2016
DOI: 10.1111/grs.12133
|View full text |Cite
|
Sign up to set email alerts
|

Generation of paternal dihaploids in tall fescue

Abstract: Within the Lolium‐Festuca genome complex there is a need for modern breeding approaches that can facilitate the rapid development of improved germplasm or cultivars. Traditional recurrent or mass‐selection methods for population or synthetic development are labor intensive and time consuming. The recent development of dihaploid (DH) inducer lines of annual ryegrass (Lolium perenne L. subsp. multiflorum (Lam.) Husnot [syn. Lolium multiflorum Lam.]) that exhibit genome loss when hybridized with tall fescue (Loli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Festuca arundinacea Schreb.]) through seed obtained by self-fertilization was not found to pose any problems, even though this species is known to be self-incompatible (Kindiger 2016). More investigations into the vigour and fertility of perennial ryegrass DHs are needed in order to better characterize to what extend inbreeding depression affects their agronomic performance.…”
Section: Characteristics Of the Green Regenerantsmentioning
confidence: 99%
“…Festuca arundinacea Schreb.]) through seed obtained by self-fertilization was not found to pose any problems, even though this species is known to be self-incompatible (Kindiger 2016). More investigations into the vigour and fertility of perennial ryegrass DHs are needed in order to better characterize to what extend inbreeding depression affects their agronomic performance.…”
Section: Characteristics Of the Green Regenerantsmentioning
confidence: 99%
“…It is suggested that the genome differences and similarities between the IL L. multilorum genome when compared to that of L. perenne , L. multiflorum and L. arundinaceum (Hand, Cogan, Steward, & Forster, 2010; Pasakinskiene, Anamthawat‐Jonsson, Humphreys, Paplauskiene, & Jones, 1998) allow for the outcome differences between this Lolium sp. research and the earlier tall fescue study (Kindiger, 2016). This was not the case in this study where numerous haploids were identified and recovered.…”
Section: Discussionmentioning
confidence: 76%
“…F. arundinacea Schreb.) (Kindiger, 2016). This research describes the generation of haploid genotypes following the hybridization of L. multiflorum or L. perenne to the IL inducer line.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, investigations into and improvement of the agronomic performance of perennial ryegrass DHs, as well as an efficient seed production system, are required for an economically feasible production of hybrid cultivars. An alternative strategy to significantly reduce genotype specific responses to in vitro DH production, would be the development of in vivo haploid or DH inducers [92]. These would also allow the purging of deleterious alleles from natural populations, thus enabling a broadening of the genetic variation available for breeding without incurring high levels of performance impairment [99].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, segregation distortion due to in vitro androgenesis, resulting in higher allele frequencies of the donor most amenable to tissue culture, can thus be avoided [29,[87][88][89][90][91] [92]. Selection could be performed on the vigorous F 1 hybrids prior to inflorescence harvest and the subsequent recovery of 1-5 DHs per plant [93].…”
Section: Future Applications Of Haploid and Doubled Haploid Techniquementioning
confidence: 99%